Pengaruh Disiplin Kerja Dan Pengalaman Kerja Terhadap Kinerja Guru Yayasan Mas Athoriyah Cikatomas Kabupaten Tasikmalaya - Dina Triyana Sari; Arga Sutrisna; Kusuma Agdhi Rahwana (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This study aims to determine the simultaneous and partial effect of work discipline and work experience on teacher performance at the Mas Athoriyah Cikatomas Foundation, Tasikmalaya Regency. The research method used in this study is a quantitative method with a census approach. The population in this study amounted to 40 teachers at the Mas Athoriyah Cikatomas Foundation, Tasikmalaya Regency. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results of this study indicate that work discipline and work experience simultaneously have a significant effect on teacher performance at the Mas Athoriyah Cikatomas Foundation, Tasikmalaya Regency. Work Discipline partially has a significant effect on the Teacher Performance of the Mas Athoriyah Cikatomas Foundation, Tasikmalaya Regency, and work experience partially has a significant effect on the Teacher Performance of the Mas Athoriyah Cikatomas Foundation, Tasikmalaya Regency.